The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/adma.200400777
|View full text |Cite
|
Sign up to set email alerts
|

Weakly Ferromagnetic Ordered Mesoporous Co3O4 Synthesized by Nanocasting from Vinyl‐Functionalized Cubic Ia3d Mesoporous Silica

Abstract: Mesostructured metal oxides whose framework structures are engineered from materials other than silica make attractive research subjects. However, direct synthesis of these kinds of mesoporous materials using surfactants is quite difficult because, compared to silica, the surfactant/oxide composite precursors are often more susceptible to lack of condensation, redox reactions, or phase transitions accompanied by thermal breakdown of the structural integrity.[1] The nanocasting method for carbon, [2] pioneered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
178
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(197 citation statements)
references
References 19 publications
(11 reference statements)
14
178
0
5
Order By: Relevance
“…Bruce's work also confirmed that mesoporous Co 3 O 4 , Cr 2 O 3 , Fe 2 O 3 , Mn 2 O 3 , and Mn 3 O 4 catalysts exhibited high catalytic reactivity for CO oxidation [22]. Transition metal oxides are more susceptible to hydrolysis, redox or phase transition reactions, and they simultaneously possess different coordination modes as well as multiple oxidation states, hence, it is difficult to obtain their mesoporous structures [23][24][25][26][27][28]. Modified approaches such as the use of soft or hard templates, hydrothermal or microemulsion strategies have been reported for the synthesis of mesoporous materials [21,25,[29][30][31].…”
Section: Introductionmentioning
confidence: 90%
“…Bruce's work also confirmed that mesoporous Co 3 O 4 , Cr 2 O 3 , Fe 2 O 3 , Mn 2 O 3 , and Mn 3 O 4 catalysts exhibited high catalytic reactivity for CO oxidation [22]. Transition metal oxides are more susceptible to hydrolysis, redox or phase transition reactions, and they simultaneously possess different coordination modes as well as multiple oxidation states, hence, it is difficult to obtain their mesoporous structures [23][24][25][26][27][28]. Modified approaches such as the use of soft or hard templates, hydrothermal or microemulsion strategies have been reported for the synthesis of mesoporous materials [21,25,[29][30][31].…”
Section: Introductionmentioning
confidence: 90%
“…[31][32][33][34] Since this situation effectively corresponds to the presence of a ferromagnet in close proximity to an antiferromagnet, additional effects, such as exchange bias, can result (see Section 2.2.2).…”
Section: No or Magnetically Inert Surface Coatingsmentioning
confidence: 99%
“…However, bulk Co 3 O 4 usually possesses a low surface area (*20 m 2 /g) which is unfavorable to its applications either as a catalyst or as a catalyst support. Mesoporous Co 3 O 4 , on the other hand, possessing the advantages of large surface areas ([100 m 2 /g) and tunable pore structures, has attracted much attention both in material science and in catalysis [10][11][12][13][14][15]. It has been shown that mesoporous Co 3 O 4 exhibited much better catalytic performance than bulk Co 3 O 4 in CO oxidation [15,16] and in VOC removal [13].…”
Section: Introductionmentioning
confidence: 99%